PERBANDINGAN STRUKTUR, FUNGSI, DAN NILAI BUDAYA PADA LEGENDA TELAGA NGEBEL PONOROGO DAN LEGENDA DANAU RANU PASURUAN - Putri, Nuraini Saura; Nugraha, Oktavian Aditya (Universitas Negeri Surabaya, 2017)
Efforts to preserve the legendary cultural heritage and in the framework of seeking the identity of the nation as well as the diversity of ethnic groups in Indonesia, one way to do is to collect and care for folklore. This research as a means to treat foklor legend of Lake Ranu and Ngebel legend Telaga. Both legends have almost the same story, both the character and the story. The purpose of this study is to determine the similarities and differences in the two legends, through its structure, function and cultural values. Such long-term goal in this study is, to provide knowledge about oral literature research on literature students who can be used as a reference for the future. In addition, this research can also provide new knowledge for the general public about the storyline of the legend of Lake Ngebel and the legend of Lake Ranu. Based on the results of research that has been done then can be drawn a conclusion, namely: the structure there are four equations and has three differences. Something contained in the two legends have three functions, namely; as entertainment, as a means of legitimizing institutions and cultural institutions, as child educators. For the cultural values contained in these two legends are the value of Diktatik, Ethical, and Religious values